2021
DOI: 10.21037/tp-21-17
|View full text |Cite
|
Sign up to set email alerts
|

Use of the ductal curvature index to assess the risk of ductal stenting in patients with duct-dependent pulmonary circulation

Abstract: Background: To evaluate whether a quantitative curvature threshold can contribute to risk stratification of ductal stenting in patients with a duct-dependent pulmonary circulation (DDPC).Methods: A single-center retrospective analysis was performed. The ductal curvature index (DCI) was calculated in 71 patients with DDPC. The ducts were divided into four classes based on quartile thresholds of DCI: class I (≤0.12), class II (0.13-0.33), class III (0.34-0.44), and class IV (≥0.45). The primary outcome of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…All published comparisons between MBTs and DS were performed regardless of the complexity of ductal morphology ( 10 13 ). In a previous study published in 2021 ( 9 ), the results of our center showed that the patients with an increased ductal tortuosity and ductal curvature index (equal to or more than 0.45) have to be classified as the high-risk patients for duct stenting. The primary outcome in these patients was achieved in only 20% of them.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…All published comparisons between MBTs and DS were performed regardless of the complexity of ductal morphology ( 10 13 ). In a previous study published in 2021 ( 9 ), the results of our center showed that the patients with an increased ductal tortuosity and ductal curvature index (equal to or more than 0.45) have to be classified as the high-risk patients for duct stenting. The primary outcome in these patients was achieved in only 20% of them.…”
Section: Discussionmentioning
confidence: 93%
“…Contrary to the results of the previous studies, the current results showed that the need for PA-plasty was higher in the DS group. This can be explained by the highly tortuous ducts associated with a resulting functional pulmonary stenosis in our DS cohort ( 9 ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations